The Influence of Marketing Strategies on Consumer Behavior: Case Study: Yotta Brand Local from Makassar - Musa, Chalid Imran (International Humanity Advance, Business & Sciences, 2024)
Organizational behavior influences efforts to improve performance, which is very important for an organization's marketing management. Marketing management is needed by the Yotta product beverage business to identify weaknesses and opportunities that can be managed using carefully planned strategies to achieve optimal goals. The focus of this research is the Yotta brand, namely how customers act towards it when they receive services according to organizational strategy or brand. Interview research is a type of qualitative research in which researchers gather to get information about the research variables. The research population is Yotta brand customers. To reach clear and unbiased conclusions, the writer uses a qualitative descriptive research style. The Yotta brand can be defined as a brand that relies on the superiority of the products it sells; However, the product marketing strategy remains important. To get customers, Yotta products use various marketing strategies. Customer behavior towards Brand Yotta's marketing strategy is expected to achieve good satisfaction with various implementations of these strategies for local Yotta brand products. They must analyze customer needs, provide clear price comparison options, and establish good communication and customer service. Therefore, the Yotta Brand must continue to strive and be consistent in providing customers with good products. In addition, it must continue to produce innovations that are in accordance with the environment and in accordance with the changing times, which will have a positive impact.